PENGEMBANGAN SELF IMPROVEMENT BOOK UNTUK MENINGKATKAN BODY IMAGE POSITIF PADA SISWA - Dewi Sartika; Evi Afiati; Rochani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the phenomenon of negative body image in schools. Based on a needs assessment conducted on 330 tenth-grade students at MAN 1 Kota Serang, the results showed that the average body image score of the respondents was 73% (moderate category). The distribution analysis indicated that 14% were low, 73% were moderate, and 13% were high. This study aims to develop a self-improvement book to enhance positive body image among students with negative body image. The method used in this study is Research & Development (R&D) employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The product was developed through a product validity testing phase by experts. The results of the expert validity for the media and content were 87% (Highly Acceptable), language expert validity was 78.57% (Acceptable), and practitioner validity was 97.91% (Highly Acceptable). Consequently, the average score from the overall evaluation was 88.97%, falling into the “Highly Acceptable” category for implementation. Additionally, the results of the pretest and posttest indicated an improvement in body image levels among the limited test subjects. Therefore, the self-improvement book is deemed highly suitable and effective for use as a guidance and counseling tool to help address negative body image among students.